Performance of the school psychologist in inclusive education - Schmengler, Angélica Regina (2022)
This research comes from discussions, carried out in the academy, about relevant practices for inclusive education. The aim was to verify the role of the School Psychologist for the inclusion of target audience students of Special Education. It is defined as qualitative, exploratory, bibliographic research. To support the reflections presented, references to School Psychology were used, in addition to legal documents, such as public policies. A search was carried out by digital means, in journals in the area of Education and Psychology, in productions with Qualis A2 and B1, which discuss the performance of School Psychology in an inclusive educational context. The findings showed that the School Psychologist has a relevant role in the inclusive process, in order to act in different spaces and levels of schooling. The school psychologist can contribute with its practices, in the orientation of teachers, students and the entire school community. The number of publications revealed the need to expand and publish research. When concluding that the gains of this action are expressive, whether for the inclusive movement, as for all the agents involved, it is urgent to publicize this work and claim the presence of the school psychologist in educational institutions.